Effects of an enteric disease challenge on growth, nitrogen retention, and immune status indicators in growing pigs - Loughmiller, J.A.; De La Llata, M.; Moser, S.; Musser, R.E.; Stott, R.D.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-five growing pigs (initially 65 ± 2 lb) were used in a metabolism study to determine the effects of a single enteric disease challenge on N retention, growth performance, and blood immunological variables. Twenty-one pigs were challenged with Salmonella typhimurium, and six pigs were assigned to an ad libitum-fed, nonchallenged control group. Eight additional nonchallenged pigs were pair-fed the feed intake of an S. typhimurium challenged counterpart. There were five 4 d collection periods (d 4 to 7, d 8 to 11, d 12 to 15, d 16 to 19, and d 22 to 25), with the S. typhimurium challenge occurring on d 8. Serum haptoglobin concentration increased in the diseasechallenged pigs, when compared to both nonchallenged treatments Growth performance and N retention were decreased temporarily during the immune challenge period but recovered to levels similar to those of nonchallenged control pigs by the end ofthe experiment on d 25. These results suggest that a single acute disease challenge may not be accompanied by large compromises in grow1h performance and lean growth rate.
Keywords: Swine; Growing pigs; Nitrogen retention; Disease challenge